Pengaruh Pemberian Dosis Pupuk Organik Cair terhadap Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) - Arma Herawati; Amelia A Limbongan; Wahida Wahida (AGRICOLA, 2018)
Liquid organic fertilizer is an alternative nutrient used by farmers. The appropriate dose of liquid fertilizer is important to ensure efficient and effective fertilization. This study aims to determine the effect of Super Flora liquid organic fertilizer doses on the growth and production of peanuts. The method used in this study was a Randomized Block Design (RCBD) with 6 (six) treatments and repeated 4 (four) times, so there were 24 experimental units. The results showed that the treatment of liquid super organic fertilizer did not have a significantly different effect on the observed variables on the growth component of peanut plants, but had a significantly different effect on the production component, namely the stover wet weight (g), number of pods per sample, and weigh 100 seeds (g). The best dose for peanut production based on research is 5 cc/ l water, this shows the highest production yield of 1,313 g/ plot, equivalent to 3.47 tons/ha.